Human hamstring tenocytes survive when seeded into a decellularized porcine Achilles tendon extracellular matrix. (22nd August 2013) - Lohan, Anke; Stoll, Christiane; Albrecht, Marit; Denner, Andreas; John, Thilo; Krüger, Kay; Ertel, Wolfgang; Schulze-Tanzil, Gundula
Abstract: Tendon ruptures and defects remain major orthopaedic challenges. Tendon healing is a time-consuming process, which results in scar tissue with an altered biomechanical competence. Using a xenogeneic tendon extracellular matrix (ECM) as a natural scaffold, which can be reseeded with autologous human tenocytes, might be a promising approach to reconstruct damaged tendons. For this purpose, the porcine Achilles (AS) tendons serving as a scaffold were histologically characterized in comparison to human cell donor tendons. AS tendons were decellularized and then reseeded with primary human hamstring tenocytes using cell centrifuging, rotating culture and cell injection techniques. Vitality testing, histology and glycosaminoglycan/DNA quantifications were performed to document the success of tendon reseeding. Porcine AS tendons were characterized by a higher cell and sulfated glycosaminoglycan content than human cell donor tendons. Complete decellularization could be achieved, but led to a wash out of sulfated glycosaminoglycans. Nevertheless, porcine tendon could be recellularized with vital human tenocytes. The recellularization led to a slight increase in cell number compared to the native tendon and some glycosaminoglycan recovery. This study indicates that porcine tendon can be de- and recellularized using adult human tenocytes. Future work should optimize cell distribution within the recellularized tendon ECM and consider tendon- and donor species-dependent differences.